Kepemimpinan Rohani dan Motivasi Kerja dalam Mempengaruhi Kinerja Guru di sebuah Sekolah Kristen - sugiono, luciana (Jurnal Ketopong Pendidikan, 2023)
The quality of education within an institution is highly dependent on the quality of teacher performance, as teachers play a central role in shaping students learning experiences and outcomes. Therefore, it is essential for educational institutions to conduct teacher performance evaluations regularly to maintain and enhance educational quality. Various factors influence teacher performance, including the leadership style of the principal and the teachers’ level of work motivation. This study aimed to analyze the positive influence of spiritual leadership and work motivation on teacher performance. The research employed a quantitative approach using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method to examine the relationships among the variables. Data were collected through questionnaires distributed to fifty teachers at XYZ Elementary School. The findings reveal that the principal’s spiritual leadership significantly enhances teachers’ work motivation, which in turn improves their performance. Moreover, both spiritual leadership and work motivation were found to have a positive and direct impact on teacher performance. These results highlight the importance of spiritual values in leadership practices and the need for schools to foster motivation among teachers to achieve better educational outcomes and overall institutional effectiveness.